CULTURAL IDENTITY CRISES IN JESSICA HAGEDORN’S DOGEATERS - Rosa Maria Simamora (Muse: Jurnal of Art, 2022)
This research reveals cultural identity crises in Jessica Hagedorn’s Dogeaters. As an American Book Award Winner, Hagedorn represents certain countries undergoing the crises through phenomena such as excessive consumerism, sexual and drug abuses, and corrupt government. This is a library research where all data are taken from the library through extensive reading and internet browsing, and applies socio-cultural and mimetic approaches. Mimetic approach proposing by Abrams views that literature is the imitation of the real world, while socio-cultural approach proposing by Grebstein assumes that literary works cannot be fully understood apart from the culture or milieu that produces it. Cultural identity crises is focused on consumerism, drug and sexual abuses, corrupt goverment shown through characters, plot, point of view, image, language, and references. This research finds that Jessica Hagedorn in her novel Dogeaters vividly and beautifully conveys cultural identity crises undergoing by the ex-colonized countries, besides, crises is the result of negative impacts of globalization